2015
DOI: 10.1055/s-0034-1383410
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Emodin on Amyloid-β 25–35-Induced Neurotoxicity in AβPP/PS1 Mice and PC12 Cells through Activation of the Class III Phosphatidylinositol 3-Kinase/Beclin-1/B-Cell Lymphoma 2 Pathway

Abstract: Autophagy plays an important role in the pathogenesis of Alzheimer's disease. In the present study, the blockade mechanism of emodin on amyloid-β 25-35-induced neurotoxicity was explored. Cell viability of PC12 cells was evaluated by the MTT assay and neuro damage by the lactate dehydrogenase leakage assay. Gene silencing by small interfering RNA, cDNA constructs and transfection, as well as Western blot were performed to assess protein expression levels. AβPP/PS1 mice were administered orally with emodin (50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…PC12 cells were derived from a tumor found in the rat adrenal medulla with catecholaminergic neuronal properties [56]. PC12 cells have been extensively used as a model to study the neurotoxicity of numerous stimulants in vitro [57][58][59]. Our data demonstrated that treatment of PC12 cells with corticosterone obviously decreased the cell viability, indicating the neurotoxic effect of corticosterone on PC12 cells.…”
Section: Discussionmentioning
confidence: 68%
“…PC12 cells were derived from a tumor found in the rat adrenal medulla with catecholaminergic neuronal properties [56]. PC12 cells have been extensively used as a model to study the neurotoxicity of numerous stimulants in vitro [57][58][59]. Our data demonstrated that treatment of PC12 cells with corticosterone obviously decreased the cell viability, indicating the neurotoxic effect of corticosterone on PC12 cells.…”
Section: Discussionmentioning
confidence: 68%
“…The accumulation of β‐amyloid protein (Aβ) in the brain plays an important role in the pathogenesis of AD. Emodin up‐regulated Bcl‐2 and also blockaded amyloid‐β25–35‐induced autophagy through the activation of the ER/PI3K/Akt pathway and the class III phosphatidylinositol 3‐kinase/Beclin‐1/B‐cell lymphoma 2 pathway, respectively (Liu et al ., ; Sun and Liu, 2015b). The results provided confirmatory evidence for the application of emodin in the prevention and treatment of AD.…”
Section: Pharmacologymentioning
confidence: 99%
“…[ 61 ] Emodin could significantly inhibit the LC3‐I/LC3‐II conversion ratio and decrease the LDH level in AβPP/PS1 mouse model and PC12 cells, which means emodin could block Aβ 25–35 ‐induced autophagy in vivo and in vitro . [ 62 ] Emodin could reduce the levels of Aβ and tau phosphorylation, decrease the levels of β‐site amyloid precursor protein‐cleaving enzyme 1 (BACE1) and improve the activity of protein phosphatase 2A, which represents a novel potential candidate agent for AD‐like features. [ 63 ] Emodin attenuates interleukin (IL)‐1β secretion via the inhibition of NLRP3 inflammasome, which induced by ATP in LPS‐induced endotoxin mouse models.…”
Section: Quinones and Its Role In Admentioning
confidence: 99%